Integrated Satellite-Terrestrial Networks: Architectures, Key Techniques, and Experimental Progress - Sun, Yaohua; Peng, Mugen; Zhang, Shijie; Lin, Guangrong; Zhang, Peng (IEEE network, 2022)
As a promising paradigm toward the sixth generation mobile communication, integrated satellite-terrestrial networks (ISTNs) can greatly extend network coverage and reduce the dependence on terrestrial infrastructure. Despite the charming potentials of ISTN, many challenges are still unsolved in terms of architectures, air interface protocol enhancement, mobility management, experimental validation, and so on. Therefore, in this article, we first clarify the four stages of ISTN architecture development and then discuss protocol enhancements as well as key techniques for ISTN. In addition, one of our previous experiments is reported in detail, where low Earth orbit satellite communication is used as the backbone connecting two private 5G networks that are 400 km away from each other. During the experiment, a remote immersive robot control service is realized with average end-to-end latency and uplink peak data rate being 30 ms and 50 Mb/s, respectively, which shows the feasibility of ISTN in supporting emerging industrial Internet applications. Meanwhile, other experimental progress is also presented, focusing on air interface protocol enhancement, transmission control protocol transmission, and network management. Finally, we point out future trends in ISTN, including programmable satellites and artificial-intelligence-based networking.